Declining awareness of HPV and HPV vaccine within the general US population. Issue 2 (1st February 2021) - Chido-Amajuoyi, Onyema Greg; Jackson, Inimfon; Yu, Robert; Shete, Sanjay
ABSTRACT: Programs aimed at boosting human papillomavirus (HPV)-related awareness are considered one of the most effective strategies for increasing vaccination uptake and eliminating HPV-associated cancers. Several US states have made strong commitments to this effort through legislation and dedicated funds. However, it is not known if these efforts have resulted in population-level increments in HPV awareness overtime. Using the Health Information National Trends Survey data, we examined the awareness of HPV and HPV vaccine in the US, between 2008 and 2018. Prevalence estimates and confidence intervals were calculated for HPV and HPV vaccine awareness. Further, we assessed awareness after stratifying by key sociodemographic characteristics. Overall, the awareness of HPV and HPV vaccine declined over time. The lowest awareness was among racial minorities, rural residents, male respondents, those aged 65 years and older, as well as those with the lowest educational and socioeconomic standing. Between 2013 and 2018, the awareness of HPV and HPV vaccine declined by almost 10% among males, those with a high school level of education or lower, and those who earned less than USD 35, 000 per annum. In 2018, the awareness of HPV and HPV vaccine was highest among non-Hispanic whites (65.8% and 66.5%) and female adults (70.5% and 71.4%); however, these figures represented declines of about 5% from rates observed in 2008. Amidst a background of sub-optimal HPV vaccination uptake and a growing incidence of HPV-associated cancers in the US, HPV-related awareness within the general US population has declined over time. This calls for stricter enforcement of legislation aimed at boosting HPV awareness, as well as frequent evaluation of government-funded HPV awareness programs.